Synthesis, spectral and thermal properties of some high coordinated complexes of thorium(IV) and dioxouranium(VI) derived from 4[N-(2’-hydroxy-1’-naphthalidene)-amino]antipyrinethiosemicarbazone - Ram K.Agarwa; Rajeev Garg; S.K.Sindhu (Bulletin of the Chemical Society of Ethiopia, 2005)
In present work, we describe the synthesis of thorium(IV) and dioxouranium(VI) coordination compounds of 4[N-(2’-hydroxy-1’-naphthalidene)amino]antipyrinethio- semicarbazone (HNAAPTS) with the general composition ThX4.n(HNAAPTS) (X = Cl, Br, I, NCS or ClO4, n = 2; X = NO3, n = 1) and UO2X2.n(HNAAPTS) (X = Br, I, NCS or ClO4, n = 2, X = NO3 or CH3COO, n = 1). All the coordination compounds were characterized by analytical, molar mass, molar conductance and infrared studies. The infrared spectral studies reveal that the ligand HNAAPTS is coordinated in neutral tridentate (N,N,S) fashion. The coordination number of Th(IV) in these coordination compounds varies from 6, 8, 10 or 11; while for U(VI) the coordination number are 8, 9 or 10. Thermal stabilities of these complexes were investigated through thermogravimetric analysis.